The Evaporation of Manganese from Liquid Iron Under Reduced Pressures in the Temperature Range 1320C to 1810C - Aurini, Terrence (My University, 1964)
This thesis presents a review of the theory of evaporation of pure substances with respect to kinetic and mechanistic models. These concepts are applied to multi-component evaporation and a model for the evaporation of solute atoms from a solvent is postulated. The evaporation experiments were performed on Fe 1% Mn melts at a constant pressure of approximately 10 microns over a temperature range of 1320° to 1810°C. The correlation between the experimental results and the expected theoretical results is discussed thoroughly in terms of surface control and diffusion control.
Keywords: evaporation; manganese; liquid iron; reduced pressure; temperature range